Successful Treatment of Myeloid Sarcoma in an Elderly Patient with Myelodysplastic Syndrome with Reduced-Dose Azacitidine - Kazuya Sato; Nodoka Tsukada; Junki Inamura; Shigetsuna Komatsu; Keisuke Sato; Masayo Yamamoto; Motohiro Shindo; Kentaro Moriichi; Yusuke Mizukami; Mikihiro Fujiya; Yoshihiro Torimoto; Toshikatsu Okumura (Case Reports in Hematology)
Myeloid sarcoma (MS), which involves extramedullary lesions, is classified as a unique subtype of acute myeloid leukemia (AML). At present, no standard treatments for MS have been established. The patient was an 89-year-old man with myelodysplastic syndrome-excess blast-2 (MDS-EB-2) with a 2-year history of intermittent treatment with azacitidine (AZA) during a 4-year history of MDS. He developed painful cutaneous tumors 8 months after the second discontinuation of AZA. They were refractory for antibiotics and topical tacrolimus hydrate. A tumor biopsy was performed, and the histological findings of the tumor lesion showed a proliferation of tumor cells that were positive for myeloperoxidase and CD68 and negative for CD4 and CD123. The patient was diagnosed with MDS-associated MS. MDS-EB-2 quickly progressed to AML with the appearance of peripheral blood blasts and 25% bone marrow blasts. Monotherapy with reduced-dose AZA (37.5 mg/m2 for 7 days, every 4–6 weeks) was restarted, and the MS quickly disappeared. The patient’s MS was successfully treated with 16 cycles of AZA treatment over a 22-month period. There have been 10 reported cases in which MS was successfully treated with AZA. Among the 10 cases, the patient in the present case was the oldest. Treatment with reduced-dose AZA should be considered as a therapeutic option for MS in elderly patients with MDS, especially patients who are ineligible for intensive chemotherapy.